Current Immunotherapies for Glioblastoma Multiforme - Huang, Boyuan; Li, Xuesong; Li, Yuntao; Zhang, Jin; Zong, Zhitao; Zhang, Hongbo (Frontiers in Immunology, 2021)
Glioblastoma Multiforme (GBM) is the most common and aggressive primary malignant tumor in the central nervous system. The current standard treatment includes maximal safe surgical resection, radiation and chemotherapy demonstrated limited efficiency in improving patients prognosis. Immunotherapy, which predominantly focuses on peptide vaccines, DC vaccines, CAR-T cells and checkpoints inhibitors therapy, have achieved some promising results in both preclinical and clinical trials. The future of immune therapy for GBM requires an integrated effort, with rational combinations of vaccines therapy, cell therapy, radio- and chemotherapy, as well as molecules therapy targeting TME.